2016
DOI: 10.4172/pharmaceutical-sciences.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Dimethylamine and Triethylamine in Hydrochloride Salts of Drug Substances by Headspace Gas Chromatography using Dimethyl Sulphoxide- imidazole as Diluent

Abstract: A simple, rapid, accurate and precise analytical method for determination of secondary and tertiary amines in hydrochloride salt form of drug substances in non-aqueous medium, which does not require any derivatization, was developed by headspace gas chromatography. Dimethylamine hydrochloride and triethylamine hydrochloride were analyzed in metformin hydrochloride. The sample was dissolved in a vial containing dimethyl sulphoxide and imidazole. The vials were incubated at 100°, for 20 min. The syringe temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The calculated LOD of DMA was 0.960 and 0.718 μg/L using the CS16 and CS19 columns, respectively. The LOD of DMA is about 1000 times lower than headspace gas chromatography method (930 μg/L) [ 17 ]. The reported LOD of DMA is 5.4 μg/L by HPLC with diode array detection after derivatization with halonitrobenzenes, and 0.75 μg/L by hydrophilic interaction chromatography coupled with mass spectrometry detection (HILIC-MS) [ 11 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculated LOD of DMA was 0.960 and 0.718 μg/L using the CS16 and CS19 columns, respectively. The LOD of DMA is about 1000 times lower than headspace gas chromatography method (930 μg/L) [ 17 ]. The reported LOD of DMA is 5.4 μg/L by HPLC with diode array detection after derivatization with halonitrobenzenes, and 0.75 μg/L by hydrophilic interaction chromatography coupled with mass spectrometry detection (HILIC-MS) [ 11 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The method requires a lengthy derivatization process in order to achieve the highest yield. A headspace gas chromatography (GC) method for DMA determination does not require derivatization [ 12 ]. However, the GC method requires sample preparation to convert the salt form of the amine to the free base.…”
Section: Introductionmentioning
confidence: 99%
“…Most pharmaceutical companies utilize the guidelines provided by the European Medicines Agency and the ICH M7(R1) to regulate toxic impurities in drug substances (European Medicines Agency, 2006;ICH Harmonised Guideline, 2017). Following this, further research studies have been conducted to assess the carcinogenic and genotoxic contaminants found in pharmaceutical drug substances using a variety of analytical techniques including HPLC, ultra-performance liquid chromatography, GC, LC-tandem mass spectrometry, and GC-MS. (Babu et al, 2018;Balaji et al, 2022;Balaji & Sultana, 2017;Chen et al, 2020;Chittireddy et al, 2023;Feng et al, 2016;Gopalakrishnan & Devi, 2016;Grace et al, 2019;Kosuri et al, 2023;Lee et al, 2022;Louati et al, 2018;Narapereddy & Alladi, 2023;Nekkala et al, 2017;Neyer et al, 2020;Pandey et al, 2011;Sajan et al, 2015;Siva Jyothi & Venkatnarayana, 2021;Sojitra et al, 2019;Tatipamula et al, 2019;Uppala & Arthanareeswari, 2021;Vijaya Bhaskar Reddy et al, 2014;Wang et al, 2016;Yelampalli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to LC, well established GC methods exist for the analysis of alkylamines in different media using modern capillary columns [31][32][33] . However, due to the highly polar and reactive nature of primary, secondary and lower aliphatic tertiary amines, their performance on the routine capillary GC columns is unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%